Environmental management in basic education: the reality of schools in the State schools in Iguatu, Ceará, Brazil - Rodrigues, Alzeir Machado; Menezes, Jones Baroni Ferreira de; Rodrigues, Maria Virlene de Araujo; Abreu, Môngolla Keyla Freitas de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Environmental management has been a much discussed topic in the world, in the face of human actions, consisting of a form of administration that seeks to minimize the effects to the environment. Therefore, the need to develop an environmental management in the school environment is observed, which an investigation it is necessary to clarify the achievement of such a practice. This study is a descriptive research, quantitative and qualitative approach. The population sample was chosen and teachers, engineers and managers from two high schools in the city of Iguatu, Ceará, totaling 45 participants. Data collection was performed from the application of a questionnaire containing 15 objective and subjective questions, applied during the month of May 2015. The da ta were analyzed descriptively. Before observed, teachers know the term environmental management (62%), being able to raise relevant issues on preservation of natural resources. The development of environmental issues, students participate in projects related to the theme (84%) and schools almost always (58%) promote events on sustainable development and relevant issues. Among the results, it is observed that teachers have a preliminary design on environmental management, although some unfamiliar with this concep t, and that schools promote, even partially, activities which promote sustainable development.